THE ROLE OF SOCIAL ENTREPRENEURSHIP IN ENSURING THE SUSTAINABLE DEVELOPMENT OF UKRAINE - Volkova, Mylytsia; Shevchenko, Viktoriia (Social Economics, 2016)
The article gives the definition of social entrepreneurship, which is regarded as the most important resource in improving the quality of life of the population and a factor in the development of civil society. It is determined that the key to the success of the concept of social entrepreneurship in Ukraine is the development of a national strategy for the development of social entrepreneurship, which would allow to coordinate efforts of all stakeholders – entrepreneurs, NGOs, donor agencies and the state. We need a clear and coordinated work of those involved in the process, as well as funding individual projects, which will solve the problem systematically. Considers theoretical approaches to understanding the essence of social entrepreneurship and the practical aspects of this phenomenon. It is proved that in conditions of market transformation of economy of Ukraine, development of entrepreneurship is the basis of economic and social development, solving social problems, overcoming poverty and ensuring the highest standard of living of citizens. The estimation of social entrepreneurship in conditions of market economy development of Ukraine. The practical significance of scientific work is to update search forms and methods of use of social entrepreneurship in the definition of organizational and technological prospects of social entrepreneurship in Ukraine. Noted that positive changes in economic development of Ukraine – development of the nonprofit sector, encouraging the practice of social responsibility in the Ukrainian business, his tendency to rapidly learn from international experience – are good prerequisites for development of social entrepreneurship. This, in turn, is a major step toward the solution of social problems of Ukraine by combining the resources of key sectors of society.